Cultivation and Genomic Characterization of the Bile Bacterial Species From Cholecystitis Patients - Yan, Qiulong; Zhang, Siyi; Li, Shenghui; Wang, Guangyang; Zhang, Aiqin; Jin, Taiyang; Zhang, Yue; Lv, Qingbo; Xiao, Manchun; Sun, Yuanyuan; Li, Xiang; Cui, Song; et al. (Frontiers in Microbiology, 2021)
The microbes in human bile are closely related to gallbladder health and other potential disorders. Although the bile microbial community has been investigated by recent studies using amplicon or metagenomic sequencing technologies, the genomic information of the microbial species resident in bile is rarely reported. Herein, we isolated 138 bacterial colonies from the fresh bile specimens of 4 cholecystitis patients using a culturome approach and genomically characterized 35 non-redundant strains using whole-genome shotgun sequencing. The bile bacterial isolates spanned 3 classes, 6 orders, 10 families, and 14 genera, of which the members of Enterococcus, Escherichia-Shigella, Lysinibacillus, and Enterobacter frequently appeared. Genomic analysis identified 3 species, including Providencia sp. D135, Psychrobacter sp. D093, and Vibrio sp. D074, which are not represented in existing reference genome databases. Based on the genome data, the functional capacity between bile and gut isolates was compared. The bile strains encoded 5,488 KEGG orthologs, of which 4.9% were specific to the gut strains, including the enzymes involving in biofilm formation, two-component systems, and quorum sensing pathways. A total of 472 antibiotic resistance genes were identified from the bile genomes including multidrug resistance proteins (42.6%), fluoroquinolone resistance proteins (12.3%), aminoglycoside resistance proteins (9.1%), and β-lactamase (7.2%). Moreover, in vitro experiments showed that some bile bacteria have the capabilities for bile salt deconjugation or biotransformation (of primary bile acids into secondary bile acids). Although the physiological or pathological significance of these bacteria needs further exploration, our works expanded knowledge about the genome, diversity, and function of human bile bacteria.